2016
DOI: 10.15233/gfz.2016.33.6
|View full text |Cite
|
Sign up to set email alerts
|

Seiches in the Plitvice Lakes

Abstract: A campaign of high-frequency measurements of water level was carried in the two largest of the Plitvice Lakes, Prošće and Kozjak, to study seiches in the lakes. Measurements were performed at 1-min sampling rate during a 46-day interval, at two opposite ends in each lake, which also provided information on the phase relations. Power spectra were calculated to determine the periods of the normal modes. The observed peaks in the spectra were interpreted with the help of theoretical results obtained by the simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…Apart from the diurnal cycle and its higher harmonics, other significant periods emerged for some variables, such as the air pressure period of approximately 20 d, which is very likely associated with atmospheric planetary (Rossby) waves (e.g., Pasarić et al, 2000;Šepić et al, 2012). Additionally, a similar period (23 d) also appeared in the lake temperature at a depth of 23 m. However, the possible relationship with atmospheric Rossby waves is beyond the scope of the present work.…”
Section: Spectramentioning
confidence: 75%
See 2 more Smart Citations
“…Apart from the diurnal cycle and its higher harmonics, other significant periods emerged for some variables, such as the air pressure period of approximately 20 d, which is very likely associated with atmospheric planetary (Rossby) waves (e.g., Pasarić et al, 2000;Šepić et al, 2012). Additionally, a similar period (23 d) also appeared in the lake temperature at a depth of 23 m. However, the possible relationship with atmospheric Rossby waves is beyond the scope of the present work.…”
Section: Spectramentioning
confidence: 75%
“…While causes of the periodicities at ≈ 6.9 h and 49 min are not clear, periods of ≈ 9 min are driven by barotropic surface seiches. Namely, according to the observation study of Kozjak Lake, the principal mode of surface seiches is 9 min (Pasarić and Slaviček, 2016). These barotropic oscillations of the lake surface produce oscillating (upwinddownwind) lake currents that have the same period as oscillations of the lake surface.…”
Section: Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…While causes of the periodicities at ≈ 6.9 h and 49 min are not clear, periods of ≈ 9 min are driven by barotropic surface seiches. Namely, according to the observational study of Kozjak Lake, the principal mode of surface seiches is 9 min (Pasarić and Slaviček, 2016). These barotropic oscillations produce oscillating (upwind-downwind) lake currents, which due to realistic lake basin (that is, due to the inclined lake bottom) oscillate with the same period upslope and downslope.…”
Section: Spectramentioning
confidence: 99%
“…Few studies have reported on the observed physical properties of lakes, such as lakes temperatures, water conductivity and transparency (Gligora Udovič et al, 2017;Sironić et al, 2017). Some authors report on lake stratifications based only on occasional observations of temperature profiles (Gavazzi, 1919;Petrik, 1958Petrik, , 1961, while others investigated surface seiches (Gavazzi, 1919;Pasarić and Slaviček, 2016) and mentioned two possible events of internal seiches seen as vertical movements of the isothermal surfaces (Gavazzi, 1919).…”
Section: Introductionmentioning
confidence: 99%